-4(x+5)=3(x-11)

Simple and best practice solution for -4(x+5)=3(x-11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x+5)=3(x-11) equation:


Simplifying
-4(x + 5) = 3(x + -11)

Reorder the terms:
-4(5 + x) = 3(x + -11)
(5 * -4 + x * -4) = 3(x + -11)
(-20 + -4x) = 3(x + -11)

Reorder the terms:
-20 + -4x = 3(-11 + x)
-20 + -4x = (-11 * 3 + x * 3)
-20 + -4x = (-33 + 3x)

Solving
-20 + -4x = -33 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-20 + -4x + -3x = -33 + 3x + -3x

Combine like terms: -4x + -3x = -7x
-20 + -7x = -33 + 3x + -3x

Combine like terms: 3x + -3x = 0
-20 + -7x = -33 + 0
-20 + -7x = -33

Add '20' to each side of the equation.
-20 + 20 + -7x = -33 + 20

Combine like terms: -20 + 20 = 0
0 + -7x = -33 + 20
-7x = -33 + 20

Combine like terms: -33 + 20 = -13
-7x = -13

Divide each side by '-7'.
x = 1.857142857

Simplifying
x = 1.857142857

See similar equations:

| 2x-0.3-2.6x=3.42 | | 2x*5=11 | | v+5=8 | | 8=-5/6z-12 | | 2-3(3x-4)+5=52 | | -3(x+8)-2(4x-3)=-7 | | -3=5v-5 | | Xlnx=6lnx | | x+3.5=9 | | (4f+5)-(-5f-40)=180 | | -94-x=-12x+49 | | 13x^2-16x=4 | | 4(k+5)=2(9t-2) | | 4(v-8)=-2v-26 | | 8x=-8x-7x | | xsquared+12=1 | | 2x^2=x+29 | | -7(v+4)+5(6-7v)=44 | | 5d+7x+6= | | -36-3x=64-8x | | 12-8-12= | | 5-3x/4=4 | | 66*10= | | 8x-(6x+7)=6x-47 | | ×/11=×/12-8 | | 6+8-78738+3837484849=0939v | | 5x-40=10x-50 | | 6x-7-x=17 | | 58800=P-(0.00917P) | | -12=m+1-6 | | -7x-33=-9x+25 | | x+.10=70 |

Equations solver categories